Photoplethysmograph fingernail sensors for measuring finger forces without haptic obstruction. - Mascaro, S.A (IEEE Transactions on robotics and automation)
A new type of touch sensor for detecting contact pressure at human fingertips is presented. This new sensor allows the fingers to directly contact the environment without obstructing the human's natural haptic senses. The finger touch force is detected by measuring changes in the coloration of the fingernail; hence the sensor is mounted on the fingernail rather than on the fingertip. Specifically, the fingernail is instrumented with miniature light emitting diodes (LEDs) and photodetectors in order to measure changes in the reflection intensity when the fingertip is pressed against a surface. The changes in intensity are then used to determine changes in the blood volume under the fingernail, a technique termed "reflectance photoplethysmography". A hemodynamic model is used to investigate the dynamics of the blood volume at two locations under the fingernail. A miniaturized prototype nail sensor is designed, built, and tested. The theoretical analysis is verified through experiment and simulation